THE NOVEL INVALIDNÍ SOUROZENCI (DISABLED SIBLINGS) AS A GUIDE TO THE SEMIOSPHERE OF THE UNDERGROUND - Hošek, Adam (Bohemica Olomucensia, 2021)
The article explores the role of the novel Invalidní sourozenci by Egon Bondy in the semiotic space of the Czech underground during its formative period in the mid 1970s. It is viewed through Jurij Lotman's comparison between semiosphere and a museum exhibition.
Keywords: Underground; Egon Bondy; Invalidní sourozenci; semiosphere; cultural semiotics